Models of Maternal Behavior and Suggested Health Service Program Interventions for Prevention of High-Risk Pregnancy: A Systematic Literature Review - Noor Hidayah; Oktia Woro Kasmini Handayani; Ari Yuniastuti; Dina Nur Anggraini Ningrum (International Conference on Science, Education, and Technology, 2023)
'Baby steps' health interventions are scheduled in stages to improve birth outcomes. This intervention focuses on preventing high-risk pregnancies, including preventing excessive gestational weight gain (GWG) because it can cause risk of complications including maternal and child obesity and the risk of neural tube defects (NTD) in the fetus and etc. Objective: This study is to examine more deeply how the mother's behavior model and health service program interventions are recommended to increase the prevention of high-risk pregnancies. Methods: This systematic review was written based on PRISMA guidelines through three electronic databases, namely PubMed, Springer, and ScienceDirect with keywords of maternal behavior, high-risk pregnancy prevention and clinical trials and include 9 articles to be analyzed. Results: Cognitive health schemes related to perspectives that shape maternal behavior include believing that pregnancy is a 'fail safe' system where the baby in the womb will be fine, regardless of the mother's health. Therefore, the behavior that often occurs among the community is low prevention of obesity, low consumption of sufficient folic acid, wrong diet patterns, inadequate physical activity, stress, alcohol use and smoking. High-risk pregnancy prevention program interventions must be comprehensive and use intensive evidence-based data management. Conclusion: Low obesity prevention behavior, low consumption of sufficient folic acid, wrong dietary patterns, inadequate physical activity, stress, alcohol use and smoking can be overcome by implementing an intensive weight management program equipped with SMS reminders of a healthy lifestyle and education regarding the importance of intervention programs to prevent high-risk pregnancies.